2022
DOI: 10.3389/fimmu.2022.1074329
|View full text |Cite
|
Sign up to set email alerts
|

Case report: JAKi and TNFi dual therapy is a potential treatment strategy for difficult-to-treat rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a heterogeneous chronic disease. RA patients should start disease modifying anti-rheumatic drugs (DMARDs) therapy immediately after diagnosis. If first-line treatment with conventional synthetic DMARDs does not relieve the disease, biology and targeted synthetic DMARDs are options for patients. Patients can switch to different types of biological and targeted synthetic DMARDs if remission is not achieved. However, for patients with difficult-to-treat RA, achieving disease stabiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In the process of clinical application, it was found that, according to the clinical symptoms of patients and different activity stages of RA, two different antirheumatic drugs or antirheumaticdrugs could be combined with nonsteroidal anti-inflammatory drugs and glucocorticoids according to the clinical symptoms of patients and different activity stages of RA. This combined scheme not only achieves therapeutic effects but also increases treatment costs and adverse reactions, besides, Thus, owing to the long treatment cycle and high price of RA treatments and the large number of patients with RA who show poor drug compliance, the treatment effect is reduced and medical resources are wasted ( 243 ).…”
Section: Immunotherapy For Rheumatoid Arthritis and Postmenopausal Os...mentioning
confidence: 99%
“…In the process of clinical application, it was found that, according to the clinical symptoms of patients and different activity stages of RA, two different antirheumatic drugs or antirheumaticdrugs could be combined with nonsteroidal anti-inflammatory drugs and glucocorticoids according to the clinical symptoms of patients and different activity stages of RA. This combined scheme not only achieves therapeutic effects but also increases treatment costs and adverse reactions, besides, Thus, owing to the long treatment cycle and high price of RA treatments and the large number of patients with RA who show poor drug compliance, the treatment effect is reduced and medical resources are wasted ( 243 ).…”
Section: Immunotherapy For Rheumatoid Arthritis and Postmenopausal Os...mentioning
confidence: 99%